EFEKTIFITAS PENAMBAHAN BUAH TERHADAP KADAR GULA DARAH PADA DIABETESI TIPE 2 RAWAT INAP DI RUMAH SAKIT SANTA ELISABETH SEMARANG - Suratmi, Chatarina Sri; Jaelani, Mohammad; Susiloretni, Kun Aristiati (JURNAL RISET GIZI, 2017)
Background  : Diabetes mellitus (DM) is a group of metabolic diseases characterized by an increase in blood glucose (hyperglycemia) due to impaired insulin secretion, insulin work, or both. Results of Basic Health Research (Riskesdas) in 2013, it was found that the prevalence of DM based on doctor's diagnosis and symptoms increased with age, but from age 65 years tended to decrease.Nutrition therapy is a major component of the success of DM management such as a high-balanced diet of fiber one of them by adding fruit. Foods with high fiber can slow down digestion, absorption of glucose, cause full effects and can increase insulin sensitivity.Objective  : To know  the effectiveness of adding fruit to blood glucose levels (GDS) Diabetisi type 2.Methods  : This research is clinical nutrition research, experimental research with randomized pre and post test group control design. The sample of this study was patient type 2 diabetes in St.Elisabeth Semarang Hospital divided into 2 groups, 18 people as control group and 18 people as treatment group. Differences in the difference between the final GDS levels of the two groups were tested with Chi-Square Test in the hope that Ha was received if p 0.05.Result  : The final GDS result of the control group was 55.6% controlled while the control group was only 22.2% and Chi-Square test results showed  there was a correlation/effect of addition of 3 servings fruit  every day on blood glucose levels with p = 0.04 or p 0.05.